2003
DOI: 10.1079/bjn2003900
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant and bacterial myrosinase activity on the metabolic fate of glucosinolates in gnotobiotic rats

Abstract: The breakdown of glucosinolates, a group of thioglucoside compounds found in cruciferous plants, is catalysed by dietary or microbial myrosinase. This hydrolysis releases a range of breakdown products among which are the isothiocyanates, which have been implicated in the cancer-protective effects of cruciferous vegetables. The respective involvement of plant myrosinase and gut bacterial myrosinase in the conversion, in vivo, of glucosinolates into isothiocyanates was investigated in sixteen Fischer 344 rats. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 24 publications
5
68
2
2
Order By: Relevance
“…Only a weak relationship between the cumulative excretion of allyl isothiocyanate and phenethyl isothiocyanate was observed (r 2 ϭ 0.34). The correlation was weaker than in our previous work with rats (13,26), mainly because overall variation in urinary recovery of isothiocyanates was lower in this experiment with humans than in our previous work with rats. In previous studies with rats (13,26), we have used homologous isothiocyanates as internal standards to correct for temporal and interindividual variation in postabsorptive isothiocyanate recovery.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Only a weak relationship between the cumulative excretion of allyl isothiocyanate and phenethyl isothiocyanate was observed (r 2 ϭ 0.34). The correlation was weaker than in our previous work with rats (13,26), mainly because overall variation in urinary recovery of isothiocyanates was lower in this experiment with humans than in our previous work with rats. In previous studies with rats (13,26), we have used homologous isothiocyanates as internal standards to correct for temporal and interindividual variation in postabsorptive isothiocyanate recovery.…”
Section: Discussioncontrasting
confidence: 52%
“…The correlation was weaker than in our previous work with rats (13,26), mainly because overall variation in urinary recovery of isothiocyanates was lower in this experiment with humans than in our previous work with rats. In previous studies with rats (13,26), we have used homologous isothiocyanates as internal standards to correct for temporal and interindividual variation in postabsorptive isothiocyanate recovery. In the previous work, we found that isothiocyanate recovery varied widely between individuals and occasions (between 10% and 65% of administered allyl isothiocyanate recovered) but that recovery of different isothiocyanates covaried within an individual [r 2 ϭ 94% for correlation between urinary allyl mercapturic acid output and urinary butyl mercapturic acid output after an oral dose of 50 mol to rats (13)].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The low recoveries of intact glucosinolates and their metabolites in faeces of animals fed glucosinolates or isothiocyanates suggest that a substantial proportion of ingested glucosinolates and isothiocyanates are metabolised in vivo (Slominski et al 1988;Bollard et al 1997;Rouzaud et al 2003). However, there is little information on the hydrolysis of glucosinolates during and after consumption of brassica vegetables by human subjects.…”
Section: Digestive and Post-absorptive Fate Of Glucosinolates After Imentioning
confidence: 93%
“…The digestive and post-absorptive fate of glucosinolates in rodents and human subjects may be influenced by an array of factors such as the activity of plant myrosinase ingested, the extent of chewing, the nature of the meal containing brassica, the composition of the gut microflora and genotypic variation in post-absorptive metabolism (Shapiro et al 2001;Rouzaud et al 2003;Seow et al 2005).…”
mentioning
confidence: 99%